Development of a Nanocluster-Based Platform for Determination of Sofosbuvir - Zahra Karimzadeh; Abolghasem Jouyban; Elaheh Rahimpour (Pharmaceutical Sciences, 2022)
Background: Sofosbuvir is a potent direct-acting antivirus agent that has been listed as a promising medicine for the treatment of all genotypes of hepatitis C virus. As antiviral drugs could be metabolized to their associated compounds and toxicologically and pharmacologically interfere with the parent drugs, identifying the therapeutic range of drugs would be notable. Methods: In the current study, copper nanoclusters (Cu NCs) are synthesized during the reduction of copper nitrate with hydrazine hydrate in a protected media and used as a nanoprobe for the determination of sofosbuvir in plasma samples. Herein, synchronous fluorescence spectroscopy (SFS) is used for monitoring of fluorescence variation of nanoprobe owing to the excessive benefits compared with the traditional fluorescence. Results: SFS peak of Cu NCs has appeared at 355 nm with ∆λ=80 nm which is decreased in the presence of sofosbuvir. To optimize the reaction factors, a response surface methodology is used and in the optimized conditions, a linear concentration-response plot is obtained in a range of 0.05-6.0 µg mL−1 with a limit of detection of 0.0147 µg mL−1. Conclusion: The developed method also reveals good repeatability and selectivity for sofosbuvir in plasma samples.